The Theory Behind the Age-Related Positivity Effect - Reed, Andrew E.; Carstensen, Laura L. (Frontiers in Psychology, 2012)
The “positivity effect” refers to an age-related trend that favors positive over negative stimuli in cognitive processing. Relative to their younger counterparts, older people attend to and remember more positive than negative information. Since the effect was initially identified and the conceptual basis articulated (Mather & Carstensen, 2005) scores of independent replications and related findings have appeared in the literature. Over the same period, a number of investigations have failed to observe age differences in the cognitive processing of emotional material. When findings are considered in theoretical context, a reliable pattern of evidence emerges that helps to refine conceptual tenets. In this article we articulate the operational definition and theoretical foundations of the positivity effect and review the empirical evidence based on studies of visual attention, memory, decision-making, and neural activation. We conclude with a discussion of future research directions with emphasis on the conditions where a focus on positive information may benefit and/or impair cognitive performance in older people.